Two-mode complex network modeling of dengue epidemic in Selangor, Malaysia - Mahmood Malik, Hafiz Abid; Mahesar, Abdul Waheed; Abid, Faiza; Wahiddin, Mohamed Ridza (IEEE, 2014)
There are many examples of complex systems in the world. These systems are very difficult to analyze due to huge number of interacting elements and complex interaction patterns between the elements. These systems can be properly analyzed by converting them into complex networks, where nodes can represent elements of the systems and links depicts the interaction patterns between these elements. Recently, many dengue fever cases are reported in Malaysia which shows the exponential increase of this fever in the country. In this paper we have formalized the dataset of dengue fever cases in Malaysia into two-mode complex network to analyze its impact on the localities. By applying network analysis metrics this research has revealed that few locations have high impact of dengue and they should be treated as critical to minimize the overall impact of spreading